1999
DOI: 10.1002/(sici)1096-8628(19991215)88:6<634::aid-ajmg11>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and dopamine receptors (D2 and D4): Linkage studies in families of alcoholics

Abstract: Activation of the mesolimbic dopamine pathway appears to promote drug- and alcohol-seeking behavior in laboratory animals. Results for association and linkage analysis between various alcohol dependence phenotypes and the dopamine receptors have been quite mixed. Similarly, both positive and negative results have been presented concerning dopamine receptor genes and temperament. Cloninger has postulated that the novelty seeking factor from the Tridimensional Personality Questionnaire (TPQ) may be related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 52 publications
2
22
1
Order By: Relevance
“…[19][20][21][22][23][24] This also led to the inclusion of a paper in press. 25 In the case of five studies, correspondence with the authors indicated that it would not be possible to include their data in the metaanalysis.…”
Section: Data Extractionsupporting
confidence: 65%
See 1 more Smart Citation
“…[19][20][21][22][23][24] This also led to the inclusion of a paper in press. 25 In the case of five studies, correspondence with the authors indicated that it would not be possible to include their data in the metaanalysis.…”
Section: Data Extractionsupporting
confidence: 65%
“…[7][8][9][11][12][13][14][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The characteristics of the studies are described in Table 1. Of these studies, 33 were not included in the metaanalysis.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…This quality has resulted in dopamine being dubbed the ''antistress molecule'' (Blum et al 2000). The A1 allele of the DRD2 gene has been associated with sensitivity to stress and anxiety (Bau, Almeida, and Hutz 2000;Jonsson et al 2003) and personality traits related to stress and anxiety (Hill et al 1999). The association we find between the DRD2 gene and partisanship also suggests another connection between partisanship and the punishment of freeriders observed by Smirnov et al (2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a significant relationship between the dopamine D2 receptor density and social attachment (Breier et al 1998;Farde, Gustavsson, and Jonsson;Jonsson et al 1999) as well as an association between the A1 allele and social alienation (Hill et al 1999), antisocial personality disorder (Ponce et al 2003), and avoidant personality types (Blum, Sheridan, Chen, Wood, Braverman and Cull 1997). Research on nonhuman animals also supports a connection between the D2 receptor and the formation of social attachments (Curtis et al 2006).…”
Section: Dopamine and The D2mentioning
confidence: 99%
“…Because these families had been included in a genome-wide linkage analysis [Hill et al, 2004], genotypes for microsatellites were available for further analyses. Also, previous genotyping had been done for the TaqI A and CA repeat polymorphisms from earlier work in our laboratory [Neiswanger et al, 1995;Hill et al, 1999] for a subset of individuals for whom the C957T, A-241G, and -141C Ins/Del genotyping was performed.…”
Section: Introductionmentioning
confidence: 99%